JAVMA News (Journal of the American Veterinary Medical Association, 2013)
Objective Honey bees (Apis mellifera) are food-producing animals. Veterinarians are necessary to provide appropriate antibiotic treatment for bees and can support beekeepers by learning to diagnose diseases, manage parasites, and provide nutritional and husbandry recommendations similar to other livestock industries. The objective of this study was to identify the challenges faced by veterinarians contemplating the addition of honey bee medicine to their practice. Methods In this observational, cross-sectional study, the survey was deployed via multiple electronic avenues across the US to veterinarians, veterinary technicians, and veterinary students starting on February 20, 2023. Information from the first 22 months of data collection is included herein. Survey response frequency distributions are presented as counts and percentages and associations between variables as χ2 and P values. On the basis of survey distribution channels, self-selection bias is expected to be present. Results Nearly 1,400 surveys were included in the analysis. Over half of the respondents indicated moderate to high interest in working with beekeepers. Numerous challenges were identified; the most commonly cited (40.2%) was a lack of knowledge, education, skills, and training. The challenges identified did not vary by type of practice, but did vary significantly by interest level. Conclusions While interest levels are high, many barriers to accepting beekeeping clients have been identified. Clinical relevance As a livestock species upon which we are highly dependent for food production, honey bees are suffering from an unacceptable mortality rate. There is both a need and opportunity for veterinarians to engage in this important and emerging area of practice.